Superhydrophobic modified porous ceramic membranes, their preparation and use

CN122912689APending Publication Date: 2026-10-16CHINA NAT PETROLEUM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510427506.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

大多数材料的超疏水涂层表面采用规则球形的二氧化硅、二氧化钛、氧化铁、氧化锌等纳米材料提供表面粗糙度,这种方式不仅对基体材料的超疏水改性程度有限,而且比表面较小,与粘合剂的结合能力欠佳,致使纳米颗粒易脱落

Benefits of technology

[0024] The method for preparing superhydrophobic ceramic oil-water separation membranes provided by this invention is simple, has mild reaction conditions, and is low in cost. The superhydrophobic ceramic oil-water separation membranes provided by this invention possess excellent superhydrophobic properties, resulting in higher oil-water separation efficiency; they also exhibit higher chemical stability, thermal stability, and durability, making them suitable for various operating conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912689A_ABST
    Figure CN122912689A_ABST
Patent Text Reader

Abstract

The application discloses a super-hydrophobic modified porous ceramic membrane and a preparation method thereof. The application provides the method for preparing the super-hydrophobic modified porous ceramic membrane, which comprises the following steps: performing surface modification on inorganic nano-filler with hierarchical rough morphology to obtain functionally grafted inorganic nano-filler; modifying the alumina porous ceramic sheet through polydopamine and the functionally grafted inorganic nano-filler to obtain a modified alumina ceramic sheet; and then performing low-surface-energy modification to obtain the super-hydrophobic modified porous ceramic membrane. The method for preparing the super-hydrophobic modified porous ceramic membrane is simple in process, mild in reaction condition and low in cost. The super-hydrophobic modified porous ceramic membrane has superior hydrophobic performance, high stability, good durability, high oil-water separation efficiency and is suitable for various working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a superhydrophobic modified porous ceramic membrane, its preparation, and its application. Background Technology

[0002] Superhydrophobic materials, due to their excellent surface properties such as self-cleaning, anti-fogging, corrosion resistance, drag reduction, and anti-icing, show broad application prospects in fields such as seawater desalination, wastewater treatment, and oil-water separation. Low-surface-energy chemical modification of micro / nano composite rough surfaces is an important method in the preparation of superhydrophobic materials.

[0003] Porous ceramic membrane materials, with their excellent corrosion resistance, chemical stability, high-temperature resistance, long lifespan, and adaptability to harsh environments, are widely used in industrial water treatment, oil-water separation, and membrane distillation. Therefore, ceramic materials are the preferred porous matrix material for constructing superhydrophobic surfaces. However, most ceramic membranes are made from natural superhydrophilic materials; to prepare superhydrophobic materials, the ceramic matrix must undergo special superhydrophobic wettability modification.

[0004] Despite the development of numerous superhydrophobic materials, several problems remain. Most superhydrophobic coatings utilize regularly spherical nanomaterials such as silica, titanium dioxide, iron oxide, and zinc oxide to provide surface roughness. This approach not only limits the degree of superhydrophobic modification of the substrate but also results in a small specific surface area and poor adhesion to binders, leading to easy detachment of nanoparticles. Furthermore, many superhydrophobic coatings use polydimethylsiloxane as a low-surface-area material, merely providing physical coating for rough structures and substrates; or they utilize fluorosilanes or long-chain alkylsiloxanes to modify the surface roughness. The resulting superhydrophobic interfaces suffer from low adhesion to the substrate, poor stability, and susceptibility to contamination and corrosion, exhibiting insufficient hydrophobic durability.

[0005] In the prior art, patent document CN102423641B discloses a method for hydrophobic modification of ceramic films, using fluorosilane as a precursor to hydrophobically modify alumina ceramic films. The synthesized hydrophobic porous ceramic surface achieves a water contact angle of 128°, but the chemical and thermal stability of the ceramic film is poor. Furthermore, the preparation process of superhydrophobic ceramic materials is complex, requiring stringent synthesis conditions, making it unsuitable for industrial scale-up and production, greatly limiting the large-scale application of superhydrophobic materials. For example, patent document CN111635258B discloses a method for superhydrophobic modification of TiO2 based on ceramic films, utilizing titanium dioxide nanorods to provide a rough structure. However, this requires immersing the ceramic film in titanium dioxide seed solution, calcining at 400–500℃ for 2–3 hours, growing titanium dioxide nanorods in a high-pressure reactor, and annealing at 300–400℃. This method suffers from complex preparation processes and stringent requirements for synthesis equipment.

[0006] Therefore, employing mild synthesis conditions and readily available raw materials for the preparation of superhydrophobic ceramics is crucial for developing superhydrophobic ceramic materials with high durability and stability. Summary of the Invention

[0007] In view of the above problems, the present invention is proposed to provide a superhydrophobic modified porous ceramic membrane and a method for preparing the same, which overcomes or at least partially solves the above problems.

[0008] As one aspect of the present invention, a method for preparing a superhydrophobic modified porous ceramic membrane is provided, comprising the following steps:

[0009] (1) Immerse porous alumina ceramic sheets in a tris(hydroxymethyl)aminomethane solution, add dopamine hydrochloride and functionally grafted inorganic nanofillers in a mass ratio of 1:(1-2), adjust the pH value to 7.0-8.5, shake, remove, wash, and dry to obtain modified alumina ceramic sheets; the modified alumina ceramic sheets are alumina ceramic sheets modified by polydopamine and inorganic nanofillers;

[0010] The functionally grafted inorganic nanofiller is one or any combination of surface-aminated mesoporous nano-silica, surface-thiolized mesoporous nano-silica, surface-aminated tetraneedle zinc oxide, and surface-thiolized tetraneedle zinc oxide.

[0011] (2) The modified alumina ceramic sheet is immersed in an ethanol solution containing a fluorine-containing low surface energy regulator, shaken, removed, washed, and dried to obtain a superhydrophobic modified porous ceramic membrane.

[0012] In a specific implementation, in step (1), the concentration of the trihydroxymethylaminomethane solution is 5-10 mmol / L.

[0013] In a specific implementation, in step (2), the concentration of the fluorinated low surface energy regulator in the ethanol solution of the fluorinated low surface energy regulator is 20-30 mg / mL.

[0014] In a specific implementation, the fluorinated low surface energy modifier is one of 2,2,3,3,4,4,4-heptafluorobutylamine and 1H,1H,2H,2H-perfluorodecylthiol or any combination thereof.

[0015] In a specific implementation, in step (1), the oscillation time is 8 to 12 hours; in step (2), the oscillation time is 8 to 12 hours.

[0016] In a specific implementation, the method for preparing the functionally grafted inorganic nanofiller is as follows:

[0017] Inorganic nanofillers with graded rough morphology were dispersed in an ethanol solution of silane surface modifier and refluxed at boiling state for 8-12 h; centrifuged, washed, and dried to obtain functionally grafted inorganic nanofillers.

[0018] The inorganic nanofiller with a graded rough morphology is one or any combination of mesoporous nano-silica and tetraneedle-shaped zinc oxide whiskers.

[0019] In a specific implementation, the mass ratio of the inorganic nanofiller with graded rough morphology to the silane surface modifier in the ethanol solution of the silane surface modifier is 1:(1~1.2).

[0020] In a specific implementation, the concentration of the silane surface modifier in the ethanol solution of the silane surface modifier is 5-10 mg / mL, and the silane surface modifier is one of 3-aminopropyltriethoxysilane and 3-mercaptopropyltriethoxysilane or any combination thereof.

[0021] As another aspect of the present invention, it relates to the superhydrophobic modified porous ceramic membrane prepared by the above method.

[0022] As another aspect of the present invention, the application of the above-mentioned superhydrophobic modified porous ceramic membrane material in oil-water separation is involved.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] The method for preparing superhydrophobic ceramic oil-water separation membranes provided by this invention is simple, has mild reaction conditions, and is low in cost. The superhydrophobic ceramic oil-water separation membranes provided by this invention possess excellent superhydrophobic properties, resulting in higher oil-water separation efficiency; they also exhibit higher chemical stability, thermal stability, and durability, making them suitable for various operating conditions. Attached Figure Description

[0025] Figure 1 This is a scanning electron microscope image of surface-aminated mesoporous silica nanoparticles from Example 1.

[0026] Figure 2 This is a water contact angle diagram of the superhydrophobic modified porous ceramic membrane in Example 1;

[0027] Figure 3 This is a scanning electron microscope image of the superhydrophobic modified porous ceramic membrane of Example 1;

[0028] Figure 4 This is a scanning electron microscope image of surface-aminated tetraneedle zinc oxide from Example 6;

[0029] Figure 5 This is a scanning electron microscope image of the superhydrophobic modified porous ceramic membrane of Example 6. Detailed Implementation

[0030] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0031] The porous alumina ceramic sheet described in the embodiments and comparative examples of this invention is circular with a diameter of 48 mm, a thickness of 4 mm, and an average pore size of 30 μm.

[0032] Example 1

[0033] This embodiment provides a method for preparing a superhydrophobic modified porous ceramic membrane, including the following steps:

[0034] 1) Amination modification of mesoporous nano silica surface: 0.5 g of 3-aminopropyltriethoxysilane (surface modifier, KH550) was dissolved in 100 mL of ethanol, and 0.5 g of mesoporous nano silica (particle size 100 nm) was added to it. The mixture was heated to boiling and refluxed for 12 h. The nanoparticles deposited at the bottom of the centrifuge tube were collected by centrifugation, washed three times with ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain surface-aminated mesoporous nano silica.

[0035] 2) Cleaning of alumina ceramic sheets: Soak the porous alumina ceramic sheets in distilled water and ultrasonically clean them 3 times, then ultrasonically clean them 3 times with anhydrous ethanol, and dry them in a vacuum oven at 60°C for 12 hours to obtain the cleaned porous alumina ceramic sheets.

[0036] 3) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 10 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 400 mg of dopamine hydrochloride and 400 mg of surface-aminated mesoporous nano-silica were added. The pH was adjusted to 8.5, and shaking was continued for 12 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and silica-modified alumina ceramic sheet.

[0037] 4) Low surface energy modification of ceramic sheets: 400 mg of 2,2,3,3,4,4,4-heptafluorobutylamine was dissolved in 20 mL of ethanol. Polydopamine and silica-modified alumina ceramic sheets were immersed in the solution and shaken for 12 h. The sheets were then removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain a superhydrophobic modified porous ceramic membrane.

[0038] The scanning electron microscope (SEM) image of the surface-aminated mesoporous silica obtained in test step (1) is shown below. Figure 1 .Depend on Figure 1It is known that the surface-aminated mesoporous nano-silica has a micro-rough morphology with pits or grooves on the surface. This type of rough morphology with hierarchical scale helps to further improve the surface roughness of ceramic materials, and can improve the hydrophobicity of ceramic materials after being deposited on the surface of ceramic materials.

[0039] The water contact angle diagram of the superhydrophobic modified porous ceramic membrane prepared in this embodiment is shown below. Figure 2 As shown.

[0040] The microstructure of the superhydrophobic modified porous ceramic membrane prepared in this embodiment was tested, see [reference needed]. Figure 3 .Depend on Figure 3 It is known that the superhydrophobic modified porous ceramic membrane has a rough morphology with a micron / nano-level structure. This rough morphology helps to further improve the surface roughness of the ceramic material and improve the hydrophobicity of the ceramic material.

[0041] Example 2

[0042] This embodiment provides a method for preparing a superhydrophobic modified porous ceramic membrane, including the following steps:

[0043] 1) Amination modification of mesoporous nano silica surface: 0.6 g of 3-aminopropyltriethoxysilane (surface modifier, KH550) was dissolved in 100 mL of ethanol, and 0.5 g of mesoporous nano silica (particle size 100 nm) was added to it. The mixture was heated to boiling and refluxed for 8 h. The nanoparticles deposited at the bottom of the centrifuge tube were collected by centrifugation, washed 3 times with ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain surface-aminated mesoporous nano silica.

[0044] 2) Cleaning of alumina ceramic sheets: Same as step 2) in Example 1;

[0045] 3) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 10 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 400 mg of dopamine hydrochloride and 400 mg of surface-aminated mesoporous nano-silica were added. The pH was adjusted to 7.0, and shaking was continued for 12 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and silica-modified alumina ceramic sheet.

[0046] 4) Low surface energy modification of ceramic sheets: 400 mg of 2,2,3,3,4,4,4-heptafluorobutylamine was dissolved in 20 mL of ethanol. Polydopamine and silica-modified alumina ceramic sheets were immersed in the solution and shaken for 12 h. The sheets were then removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain a superhydrophobic modified porous ceramic membrane.

[0047] Example 3

[0048] This embodiment provides a method for preparing a superhydrophobic modified porous ceramic membrane, including the following steps:

[0049] 1) Amination modification of mesoporous nano-silica surface: Same as step 1) in Example 1;

[0050] 2) Cleaning of alumina ceramic sheets: Same as step 2) in Example 1;

[0051] 3) Deposition of inorganic nanofillers: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 5 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 200 mg of dopamine hydrochloride and 400 mg of surface-aminated mesoporous nano silica were added. The pH was adjusted to 8.5, and shaking was continued for 8 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and silica-modified alumina ceramic sheet.

[0052] 4) Low surface energy modification of ceramic sheets: 600 mg of 2,2,3,3,4,4,4-heptafluorobutylamine was dissolved in 20 mL of ethanol. Polydopamine and silica-modified alumina ceramic sheets were immersed in the solution and shaken for 8 h. After shaking, the sheets were removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain a superhydrophobic modified porous ceramic membrane.

[0053] Example 4

[0054] This embodiment provides a method for preparing a superhydrophobic modified porous ceramic membrane, including the following steps:

[0055] 1) Thiolization modification of mesoporous nano silica surface: 0.5 g of 3-mercaptopropyltriethoxysilane (surface modifier, KH590) was dissolved in 100 mL of ethanol, and 0.5 g of mesoporous nano silica (particle size 100 nm) was added to it. The mixture was heated to boiling and refluxed for 12 h. The nanoparticles deposited at the bottom of the centrifuge tube were collected by centrifugation, washed three times with ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain surface-thiolized mesoporous nano silica.

[0056] 2) Cleaning of alumina ceramic sheets: Same as step 2) in Example 1;

[0057] 3) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 10 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 400 mg of dopamine hydrochloride and 400 mg of surface-thiolized mesoporous nano-silica were added. The pH was adjusted to 8.5, and shaking was continued for 12 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and silica-modified alumina ceramic sheet.

[0058] 4) Low surface energy modification of ceramic sheets: 400 mg of 1H,1H,2H,2H-perfluorodecyl mercaptan was dissolved in 20 mL of ethanol. Polydopamine and silica-modified alumina ceramic sheets were immersed in the solution and shaken for 12 h. After shaking, the sheets were removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain a superhydrophobic modified porous ceramic membrane.

[0059] Example 5

[0060] This embodiment provides a method for preparing a superhydrophobic modified porous ceramic membrane, including the following steps:

[0061] 1) Thiolization modification of mesoporous nano silica surface: 0.5 g of 3-mercaptopropyltriethoxysilane (surface modifier, KH590) was dissolved in 100 mL of ethanol, and 0.5 g of mesoporous nano silica (particle size 100 nm) was added to it. The mixture was heated to boiling and refluxed for 12 h. The nanoparticles deposited at the bottom of the centrifuge tube were collected by centrifugation, washed three times with ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain surface-thiolized mesoporous nano silica.

[0062] 2) Cleaning of alumina ceramic sheets: Same as step 2) in Example 1;

[0063] 3) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 5 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 200 mg of dopamine hydrochloride and 400 mg of surface-thiolized mesoporous nano-silica were added. The pH was adjusted to 8.5, and shaking was continued for 8 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and silica-modified alumina ceramic sheet.

[0064] 4) Low surface energy modification of ceramic sheets: 600 mg of 1H,1H,2H,2H-perfluorodecyl mercaptan was dissolved in 20 mL of ethanol. Polydopamine and silica-modified alumina ceramic sheets were immersed in the solution and shaken for 8 h. The sheets were then removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain a superhydrophobic modified porous ceramic membrane.

[0065] Example 6

[0066] This embodiment provides a method for preparing a superhydrophobic modified porous ceramic membrane, including the following steps:

[0067] 1) Amination modification of zinc tetrane oxide surface: 0.5 g of 3-aminopropyltriethoxysilane (surface modifier, KH550) was dissolved in 100 mL of ethanol, and 0.5 g of zinc tetrane oxide was added to it. The mixture was heated to boiling and refluxed for 12 h. The solid powder deposited at the bottom of the centrifuge tube was collected by centrifugation, washed three times with ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain surface-aminated zinc tetrane oxide.

[0068] 2) Cleaning of alumina ceramic sheets: Same as step 2) in Example 1;

[0069] 3) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 10 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 400 mg of dopamine hydrochloride and 400 mg of surface-aminated tetraneedle zinc oxide were added. The pH was adjusted to 8.5, and shaking was continued for 12 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and tetraneedle zinc oxide modified alumina ceramic sheet.

[0070] 4) Low surface energy modification of ceramic sheets: 400 mg of 2,2,3,3,4,4,4-heptafluorobutylamine was dissolved in 20 mL of ethanol. Polydopamine and zinc oxide-modified alumina ceramic sheets were immersed in the solution and shaken for 12 h. The sheets were then removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain a superhydrophobic modified porous ceramic membrane.

[0071] The scanning electron microscope image of the surface-aminated tetraneedle zinc oxide obtained in test step (1) is shown below. Figure 4 .Depend on Figure 4 It is known that the surface-aminated tetraneedle zinc oxide has a multi-level branched morphology. When it is randomly deposited on the surface of ceramic materials, it can form a more complex micron / nano composite rough morphology, which helps to improve the surface roughness of porous ceramics and enhance the hydrophobic modification effect of ceramics.

[0072] The microstructure of the superhydrophobic modified porous ceramic membrane prepared in this embodiment was tested, such as... Figure 5 As shown. By Figure 5 It is known that the superhydrophobic modified porous ceramic membrane has a rough morphology with a micron / nano-level structure. This rough morphology helps to further improve the surface roughness of the ceramic material and improve the hydrophobicity of the ceramic material.

[0073] Example 7

[0074] This embodiment provides a method for preparing a superhydrophobic modified porous ceramic membrane, including the following steps:

[0075] 1) Amination modification of zinc tetrane oxide surface: 0.6 g of 3-aminopropyltriethoxysilane (surface modifier, KH550) was dissolved in 100 mL of ethanol, and 0.5 g of zinc tetrane oxide was added to it. The mixture was heated to boiling and refluxed for 8 h. The solid powder deposited at the bottom of the centrifuge tube was collected by centrifugation, washed 3 times with ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain surface-aminated zinc tetrane oxide.

[0076] 2) Cleaning of alumina ceramic sheets: Same as step 2) in Example 1;

[0077] 3) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 10 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 400 mg of dopamine hydrochloride and 400 mg of surface-aminated tetraneedle zinc oxide were added. The pH was adjusted to 8.5, and shaking was continued for 12 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and tetraneedle zinc oxide modified alumina ceramic sheet.

[0078] 4) Low surface energy modification of ceramic sheets: 400 mg of 2,2,3,3,4,4,4-heptafluorobutylamine was dissolved in 20 mL of ethanol. Polydopamine and zinc oxide-modified alumina ceramic sheets were immersed in the solution and shaken for 12 h. The sheets were then removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain a superhydrophobic modified porous ceramic membrane.

[0079] Example 8

[0080] This embodiment provides a method for preparing a superhydrophobic modified porous ceramic membrane, including the following steps:

[0081] 1) Amination modification of zinc tetrane oxide surface: 0.5 g of 3-aminopropyltriethoxysilane (surface modifier, KH550) was dissolved in 100 mL of ethanol, and 0.5 g of zinc tetrane oxide was added to it. The mixture was heated to boiling and refluxed for 12 h. The solid powder deposited at the bottom of the centrifuge tube was collected by centrifugation, washed three times with ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain surface-aminated zinc tetrane oxide.

[0082] 2) Cleaning of alumina ceramic sheets: Same as step 2) in Example 1;

[0083] 3) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 5 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 200 mg of dopamine hydrochloride and 400 mg of surface-aminated tetraneedle zinc oxide were added. The pH was adjusted to 8.5, and shaking was continued for 8 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and tetraneedle zinc oxide modified alumina ceramic sheet.

[0084] 4) Low surface energy modification of ceramic sheets: 600 mg of 2,2,3,3,4,4,4-heptafluorobutylamine was dissolved in ethanol, and polydopamine and zinc oxide modified alumina ceramic sheets were immersed in it. After shaking for 8 hours, the sheets were taken out, washed three times with ethanol, and dried in an oven at 60°C for 12 hours to obtain a superhydrophobic modified porous ceramic membrane.

[0085] Example 9

[0086] This embodiment provides a method for preparing a superhydrophobic modified porous ceramic membrane, including the following steps:

[0087] 1) Thiolization modification of zinc tetrane oxide surface: 0.5 g of 3-mercaptopropyltriethoxysilane (surface modifier, KH590) was dissolved in 100 mL of ethanol, and 0.5 g of zinc tetrane oxide was added to it. The mixture was heated to boiling and refluxed for 12 h. The solid powder deposited at the bottom of the centrifuge tube was collected by centrifugation, washed three times with ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain surface-thiolized zinc tetrane oxide.

[0088] 2) Cleaning of alumina ceramic sheets: Same as step 2) in Example 1;

[0089] 3) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 10 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 400 mg of dopamine hydrochloride and 400 mg of surface-thiolized tetraneedle zinc oxide were added. The pH was adjusted to 8.5, and shaking was continued for 12 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and tetraneedle zinc oxide modified alumina ceramic sheet.

[0090] 4) Low surface energy modification of ceramic sheets: 400 mg of 1H,1H,2H,2H-perfluorodecyl mercaptan was dissolved in 20 mL of ethanol. Polydopamine and zinc oxide-modified alumina ceramic sheets were immersed in the solution and shaken for 12 h. The sheets were then removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain a superhydrophobic modified porous ceramic membrane.

[0091] Example 10

[0092] This embodiment provides a method for preparing a superhydrophobic modified porous ceramic membrane, including the following steps:

[0093] 1) Thiolization modification of zinc tetrane oxide surface: 0.5 g of 3-mercaptopropyltriethoxysilane (surface modifier, KH590) was dissolved in 100 mL of ethanol, and 0.5 g of zinc tetrane oxide was added to it. The mixture was heated to boiling and refluxed for 12 h. The solid powder deposited at the bottom of the centrifuge tube was collected by centrifugation, washed three times with ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain surface-thiolized zinc tetrane oxide.

[0094] 2) Cleaning of alumina ceramic sheets: Same as step 2) in Example 1;

[0095] 3) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 5 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 200 mg of dopamine hydrochloride and 400 mg of surface-thiolized tetrane zinc oxide were added. The pH was adjusted to 8.5, and shaking was continued for 8 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and tetrane zinc oxide modified alumina ceramic sheet.

[0096] 4) Low surface energy modification of ceramic sheets: 600 mg of 1H,1H,2H,2H-perfluorodecyl mercaptan was dissolved in 20 mL of ethanol. Polydopamine and zinc oxide-modified alumina ceramic sheets were immersed in the solution. After shaking for 8 h, the sheets were removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain a superhydrophobic modified porous ceramic membrane.

[0097] Comparative Example 1

[0098] This comparative example provides a method for preparing a modified porous ceramic membrane, comprising the following steps:

[0099] 1) Cleaning of alumina ceramic sheets: Soak the porous alumina ceramic sheets in distilled water and ultrasonically clean them 3 times, then ultrasonically clean them 3 times with anhydrous ethanol, and dry them in a vacuum oven at 60°C for 12 hours to obtain the cleaned porous alumina ceramic sheets.

[0100] 2) Polydopamine deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 10 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution), and 400 mg of dopamine hydrochloride was added while shaking to adjust the pH to 8.5. The shaking was continued for 12 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine-modified alumina ceramic sheet.

[0101] 3) Low surface energy modification of ceramic sheets: 400 mg of 2,2,3,3,4,4,4-heptafluorobutylamine was dissolved in 20 mL of ethanol. Polydopamine-modified alumina ceramic sheets were immersed in the solution and shaken for 8 hours. The sheets were then removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 hours to obtain a modified porous ceramic membrane.

[0102] Comparative Example 2

[0103] This comparative example provides a method for preparing a modified porous ceramic membrane, comprising the following steps:

[0104] 1) Cleaning of alumina ceramic sheets: Soak the porous alumina ceramic sheets in distilled water and ultrasonically clean them 3 times, then ultrasonically clean them 3 times with anhydrous ethanol, and dry them in a vacuum oven at 60°C for 12 hours to obtain the cleaned porous alumina ceramic sheets.

[0105] 2) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 5 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 200 mg of dopamine hydrochloride and 400 mg of zirconium terephthalate nanomaterial (UIO-66) were added. The pH was adjusted to 8.5, and shaking was continued for 8 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain alumina ceramic sheets modified with polydopamine and zirconium terephthalate nanomaterials.

[0106] 3) Low surface energy modification of ceramic sheets: 400 mg of 2,2,3,3,4,4,4-heptafluorobutylamine was dissolved in 20 mL of ethanol. Alumina ceramic sheets modified with polydopamine and zirconium terephthalate nanomaterials were immersed in the solution and shaken for 3 h. The sheets were then removed, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain a modified porous ceramic membrane.

[0107] Comparative Example 3

[0108] This comparative example provides a method for preparing a modified porous ceramic membrane, comprising the following steps:

[0109] 1) Cleaning of alumina ceramic sheets: Soak the porous alumina ceramic sheets in distilled water and ultrasonically clean them 3 times, then ultrasonically clean them 3 times with anhydrous ethanol, and dry them in a vacuum oven at 60°C for 12 hours to obtain the cleaned porous alumina ceramic sheets.

[0110] 2) Polydopamine deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 10 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution), and 400 mg of dopamine hydrochloride was added while shaking to adjust the pH to 7.0. The shaking was continued for 12 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine-modified alumina ceramic sheet.

[0111] 3) Low surface energy modification of ceramic sheets: 400 mg of octadecylamine was dissolved in 20 mL of dichloromethane, and polydopamine-modified alumina ceramic sheets were immersed in it. After shaking for 12 h, the sheets were taken out, washed three times with ethanol, and dried in an oven at 60 °C for 12 h to obtain modified porous ceramic membranes.

[0112] Comparative Example 4

[0113] This comparative example provides a method for preparing a modified porous ceramic membrane, comprising the following steps:

[0114] 1) Thiolization modification of zinc tetrane oxide surface: 0.5 g of 3-mercaptopropyltriethoxysilane (surface modifier, KH590) was dissolved in 100 mL of ethanol, and 0.5 g of zinc tetrane oxide was added to it. The mixture was heated to boiling and refluxed for 12 h. The solid powder deposited at the bottom of the centrifuge tube was collected by centrifugation, washed three times with ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain surface-thiolized zinc tetrane oxide.

[0115] 2) Cleaning of alumina ceramic sheets: Soak the porous alumina ceramic sheets in distilled water and ultrasonically clean them 3 times, then ultrasonically clean them 3 times with anhydrous ethanol, and dry them in a vacuum oven at 60°C for 12 hours to obtain the cleaned porous alumina ceramic sheets.

[0116] 3) Inorganic nanofiller deposition: The cleaned porous alumina ceramic sheet was immersed in 200 mL of a 10 mmol / L tris(hydroxymethyl)aminomethane solution (Tris solution). While shaking, 400 mg of dopamine hydrochloride and 400 mg of surface-thiolized tetraneedle zinc oxide were added. The pH was adjusted to 8.5, and shaking was continued for 12 h. The ceramic sheet was then removed, washed three times with deionized water, and dried in a 60 °C oven for 12 h to obtain polydopamine and tetraneedle zinc oxide modified alumina ceramic sheet.

[0117] 4) Low surface energy modification of ceramic sheets: Dissolve 400 mg of octadecyl mercaptan in 20 mL of ethanol, immerse polydopamine and zinc oxide modified alumina ceramic sheets in it, shake for 12 h, take them out, wash them 3 times with ethanol, and dry them in a 60 °C oven for 12 h to obtain modified porous ceramic membranes.

[0118] Hydrophobicity test:

[0119] The static water contact angles of the superhydrophobic modified porous ceramic membranes prepared in Examples 1-10 and the modified porous ceramic membranes prepared in Comparative Examples 1-4 were measured at room temperature (25°C) using a DCAT21 contact angle meter (Dataphysics, Germany). The test results are shown in Table 1.

[0120] Table 1

[0121]

[0122]

[0123] As shown in Table 1, the water contact angles of Examples 1-10 are 148.3° to 156.6°, while those of Comparative Examples 1-4 are 119.6° to 127.4°. Examples 1-10 have larger water contact angles, better hydrophobic properties, and exhibit superhydrophobicity.

[0124] Examples 1-10 use mesoporous nano-silica or tetraneedle zinc oxide with graded rough morphology to provide roughness. Dopamine hydrochloride and tris(hydroxymethyl)aminomethane are used to adhere the surface of porous alumina ceramic sheets. During the adhesion process, the amino or thiol groups on the surface of the mesoporous nano-silica or tetraneedle zinc oxide undergo chemical addition with polydopamine, and the mesoporous nano-silica or tetraneedle zinc oxide is bonded to the dopamine coating deposited on the surface of the porous alumina ceramic sheet through the amino or thiol groups on its surface. A fluorine-containing modifier is used for low surface energy modification to achieve chemical bonding superhydrophobic modification of the ceramic sheet surface, resulting in a superhydrophobic modified porous ceramic film.

[0125] Oil-water separation efficiency test:

[0126] The oil-water separation efficiency of the superhydrophobic modified porous ceramic membranes prepared in Examples 1-10 and the modified porous ceramic membrane prepared in Comparative Example 2, which has the best contact angle, was tested. The results are shown in Table 2.

[0127] The specific test method for oil-water separation efficiency is as follows:

[0128] A modified porous ceramic membrane was placed in a vacuum filter. 30 mL of chloroform and 30 mL of water were mixed to obtain an oil-water mixture, which was then poured into the vacuum filter for oil-water separation. The oil phase passed through the modified porous ceramic membrane and flowed into the filter cup below, while the aqueous phase was retained above the modified porous ceramic membrane. The masses of the separated oil and aqueous phases were weighed separately. Then, the oil-water separation efficiency was calculated according to the formula (results are shown in Table 2).

[0129] Oil-water separation efficiency (%) = m1 / m × 100%

[0130] Where m1 is the mass of the oil phase obtained after separation; m is the initial mass of the oil in the oil-water mixture.

[0131] Table 2

[0132] Serial Number Oil-water separation efficiency / % Example 1 99.3 Example 2 99.1 Example 3 99.0 Example 4 98.5 Example 5 98.6 Example 6 98.6 Example 7 98.5 Example 8 98.2 Example 9 98.2 Example 10 98.1 Comparative Example 2 93.3

[0133] As shown in Table 2, the oil-water separation efficiency of Examples 1-10 is 98.1% to 99.3%, while that of Comparative Example 2 is 93.3%, indicating that Examples 1-10 have higher oil-water separation efficiency.

[0134] Thermal stability test:

[0135] The superhydrophobic modified porous ceramic membranes prepared in Examples 1, 4, 6 and 9 and the modified porous ceramic membranes prepared in Comparative Examples 1-4 were heated at 150°C for 12 hours. The static water contact angle was measured at room temperature (25°C) using a DCAT21 contact angle measuring instrument (Dataphysics, Germany). The results are shown in Table 3.

[0136] Chemical stability test:

[0137] The superhydrophobic modified porous ceramic membranes prepared in Examples 1, 4, 6 and 9 and the modified porous ceramic membranes prepared in Comparative Examples 1-4 were soaked in sodium hydroxide solution at pH=14 for 12 h, washed three times with deionized water and ethanol respectively, and dried in an oven at 70°C for 6 h. The static water contact angle was measured at room temperature (25°C) using a DCAT21 contact angle meter (Dataphysics, Germany). The results are shown in Table 3.

[0138] Table 3

[0139]

[0140] As shown in Tables 1 and 3, after heating at 150°C for 12 hours, the water contact angle of Example 1 decreased from 156.6° to 154.4°, a decrease of 2.2°; the water contact angle of Example 4 decreased from 150.9° to 150.6°, a decrease of 0.3°; the water contact angle of Example 6 decreased from 151.6° to 150.5°, a decrease of 1.1°; and the water contact angle of Example 9 decreased from 149.5° to 148.8°, a decrease of 0.7°. The decrease in water contact angle for Examples 1, 4, 6, and 9 ranged from 0.3° to 2.2°. After heating at 150°C for 12 hours, the water contact angle of Comparative Example 1 decreased from 124.5° to 121.9°, a decrease of 2.6°; the water contact angle of Comparative Example 2 decreased from 127.4° to 122.7°, a decrease of 4.7°; the water contact angle of Comparative Example 3 decreased from 119.6° to 117.8°, a decrease of 1.8°; and the water contact angle of Comparative Example 4 decreased from 126.4° to 124.2°, a decrease of 2.2°. The decrease in water contact angle of Comparative Examples 1-4 ranged from 1.8° to 4.7°. The comparison shows that the changes in water contact angles of Examples 1, 4, 6, and 9 after heating at 150°C for 12 hours were smaller or comparable to those of Comparative Examples 1-4, indicating that Examples 1, 4, 6, and 9 possess good thermal stability.

[0141] As shown in Tables 1 and 3, after soaking in a sodium hydroxide solution with pH=14 for 12 hours, the water contact angle of Example 1 decreased from 156.6° to 154.3°, a decrease of 2.3°; the water contact angle of Example 4 decreased from 150.9° to 150.2°, a decrease of 0.7°; the water contact angle of Example 6 decreased from 151.6° to 150.1°, a decrease of 1.5°; and the water contact angle of Example 9 decreased from 149.5° to 148.3°, a decrease of 1.2°. The decrease in water contact angle for Examples 1, 4, 6, and 9 ranged from 0.7° to 2.3°. After soaking in a sodium hydroxide solution at pH 14 for 12 hours, the water contact angle of Comparative Example 1 decreased from 124.5° to 122.2°, a decrease of 2.3°; the water contact angle of Comparative Example 2 decreased from 127.4° to 123.6°, a decrease of 3.8°; the water contact angle of Comparative Example 3 decreased from 119.6° to 115.5°, a decrease of 4.1°; and the water contact angle of Comparative Example 4 decreased from 126.4° to 123.8°, a decrease of 2.6°. The decrease in water contact angle of Comparative Examples 1-4 ranged from 2.3° to 4.1°. The comparison shows that the decrease in water contact angle of Examples 1, 4, 6, and 9 after heating at 150°C for 12 hours was less than that of Comparative Examples 1-4, indicating that Examples 1, 4, 6, and 9 possess good chemical stability.

[0142] Stability testing was conducted.

[0143] The oil-water separation efficiency of the superhydrophobic modified porous ceramic membranes prepared in Examples 1, 4, 6, and 9, and the modified porous ceramic membrane prepared in Comparative Example 2 (which has the optimal contact angle) after 20 consecutive separations of oil-water mixtures was tested. The results are shown in Table 4. The specific test methods are as follows:

[0144] Oil-water separation test: The modified porous ceramic membrane was placed in a vacuum filter, and 30 mL of chloroform and 30 mL of water were mixed to obtain an oil-water mixture. The oil-water mixture was poured into the vacuum filter for oil-water separation. The oil phase flowed through the modified porous ceramic membrane into the filter cup below, while the water phase was retained above the modified porous ceramic membrane.

[0145] After removing the modified porous ceramic membrane, wipe it gently and dry it at 60°C for 1 hour;

[0146] The oil-water mixture was continuously separated 20 times. The masses of the oil phase and water phase separated in the 20th oil-water separation test were recorded. The oil-water separation efficiency of the 20th test was calculated according to the formula (the results are shown in Table 4).

[0147] Oil-water separation efficiency (%) for the 20th time = m 20 / m×100%

[0148] Where, m 20 is the mass of the oil phase obtained after the 20th separation; m is the initial mass of the oil in the oil-water mixture.

[0149] Table 4

[0150]

[0151] As shown in Tables 2 and 4, after 20 consecutive separations of the oil-water mixture, the oil-water separation efficiency of Example 1 decreased from 99.3% to 99.2%, a decrease of 0.1%; the oil-water separation efficiency of Example 4 remained unchanged; the oil-water separation efficiency of Example 6 decreased from 98.6% to 98.4%, a decrease of 0.2%; the oil-water separation efficiency of Example 9 decreased from 98.2% to 98.1%, a decrease of 0.1%; the decrease in oil-water separation efficiency of Examples 1, 4, 6, and 9 ranged from 0% to 0.2%, and the oil-water separation efficiency remained greater than 98%. After 20 consecutive separations of the oil-water mixture, the oil-water separation efficiency of Comparative Example 2 decreased from 93.3% to 91.5%, a decrease of 1.8%. The comparison shows that the decrease in oil-water separation efficiency of Examples 1, 4, and 6 after 20 consecutive separations of oil-water mixtures is much smaller than that of Comparative Example 2. Moreover, after 20 consecutive separations of oil-water mixtures, the oil-water separation efficiency of Examples 1, 4, 6, and 9 is still greater than 98%, indicating that the superhydrophobic modified porous ceramic membranes of Examples 1, 4, 6, and 9 have better stability and durability in use.

[0152] In summary, comparing the above embodiments and comparative examples, it can be seen that the embodiments of the present invention utilize mesoporous nano-silica or tetraneedle zinc oxide with a graded rough morphology to provide roughness. Surface adhesion is achieved by adding dopamine hydrochloride and tris(hydroxymethyl)aminomethane. During the adhesion process, the amino or thiol groups on the surface of the mesoporous nano-silica or tetraneedle zinc oxide undergo chemical addition with polydopamine, adhering the aminated or thiolized mesoporous nano-silica or tetraneedle zinc oxide to the surface of the porous alumina ceramic. Furthermore, superhydrophobic modification based on chemical bonding reaction is performed with a fluorine-containing low surface energy regulating agent to obtain a superhydrophobic modified porous ceramic membrane. The prepared superhydrophobic ceramic has a water contact angle of 148.3°–156.6°, exhibits superhydrophobic properties, an oil-water separation efficiency greater than 98%, and excellent stability.

[0153] The methods for preparing superhydrophobic modified porous ceramic membranes in Examples 1-10 can be summarized as follows:

[0154] (1) Immerse porous alumina ceramic sheets in a tris(hydroxymethyl)aminomethane solution, add dopamine hydrochloride and functionally grafted inorganic nanofillers in a mass ratio of 1:(1-2), adjust the pH value to 7.0-8.5, shake, remove, wash, and dry to obtain modified alumina ceramic sheets; the modified alumina ceramic sheets are alumina ceramic sheets modified by polydopamine and inorganic nanofillers;

[0155] The functionally grafted inorganic nanofiller is one or any combination of surface-aminated mesoporous nano-silica, surface-thiolized mesoporous nano-silica, surface-aminated tetraneedle zinc oxide, and surface-thiolized tetraneedle zinc oxide.

[0156] (2) The modified alumina ceramic sheet is immersed in an ethanol solution containing a fluorine-containing low surface energy regulator, shaken, removed, washed, and dried to obtain a superhydrophobic modified porous ceramic membrane.

[0157] In the above method, in step (1), the concentration of the tris(hydroxymethyl)aminomethane solution is 5–10 mmol / L;

[0158] In step (2), the concentration of the fluorinated low surface energy regulator in the ethanol solution of the fluorinated low surface energy regulator is 20-30 mg / mL;

[0159] The fluorinated low surface energy modifier is one of 2,2,3,3,4,4,4-heptafluorobutylamine and 1H,1H,2H,2H-perfluorodecylthiol or any combination thereof.

[0160] In step (1), the oscillation time is 8 to 12 hours; in step (2), the oscillation time is 8 to 12 hours.

[0161] The preparation method of the functionally grafted inorganic nanofiller in the above method is as follows:

[0162] Inorganic nanofillers with graded rough morphology were dispersed in an ethanol solution of silane surface modifier and refluxed at boiling state for 8-12 h; centrifuged, washed, and dried to obtain functionally grafted inorganic nanofillers.

[0163] The inorganic nanofiller with a graded rough morphology is one or any combination of mesoporous nano-silica and tetraneedle-shaped zinc oxide whiskers.

[0164] The mass ratio of the inorganic nanofiller with graded rough morphology to the silane surface modifier in the ethanol solution of the silane surface modifier is 1:(1~1.2).

[0165] The concentration of the silane surface modifier in the ethanol solution of the silane surface modifier is 5-10 mg / mL, and the silane surface modifier is one of 3-aminopropyltriethoxysilane and 3-mercaptopropyltriethoxysilane or any combination thereof.

Claims

1. A method for preparing superhydrophobic modified porous ceramic membranes, characterized in that, Includes the following steps: (1) Immerse the porous alumina ceramic sheet in a tris(hydroxymethyl)aminomethane solution, add dopamine hydrochloride and functionally grafted inorganic nanofiller in a mass ratio of 1:(1-2), adjust the pH value to 7.0-8.5, shake, take out, wash, and dry to obtain modified alumina ceramic sheet. The modified alumina ceramic sheet is an alumina ceramic sheet modified with polydopamine and inorganic nanofillers; The functionally grafted inorganic nanofiller is one or any combination of surface-aminated mesoporous nano-silica, surface-thiolized mesoporous nano-silica, surface-aminated tetraneedle zinc oxide, and surface-thiolized tetraneedle zinc oxide. (2) The modified alumina ceramic sheet is immersed in an ethanol solution containing a fluorine-containing low surface energy regulator, shaken, removed, washed, and dried to obtain a superhydrophobic modified porous ceramic membrane.

2. The method according to claim 1, characterized in that, In step (1), the concentration of the trihydroxymethylaminomethane solution is 5–10 mmol / L.

3. The method according to claim 1, characterized in that, In step (2), the concentration of the fluorinated low surface energy regulator in the ethanol solution of the fluorinated low surface energy regulator is 20-30 mg / mL.

4. The method according to claim 3, characterized in that, The fluorinated low surface energy modifier is one of 2,2,3,3,4,4,4-heptafluorobutylamine and 1H,1H,2H,2H-perfluorodecylthiol or any combination thereof.

5. The method according to claim 1, characterized in that, In step (1), the oscillation time is 8 to 12 hours; in step (2), the oscillation time is 8 to 12 hours.

6. The method according to claim 1, characterized in that, The preparation method of the functionally grafted inorganic nanofiller is as follows: Inorganic nanofillers with graded rough morphology were dispersed in an ethanol solution of silane surface modifier and refluxed at boiling state for 8-12 hours. Centrifugation, washing, and drying yield functionally grafted inorganic nanofillers; The inorganic nanofiller with a graded rough morphology is one or any combination of mesoporous nano-silica and tetraneedle-shaped zinc oxide whiskers.

7. The method according to claim 6, characterized in that, The mass ratio of the inorganic nanofiller with graded rough morphology to the silane surface modifier in the ethanol solution of the silane surface modifier is 1:(1~1.2).

8. The method according to claim 6, characterized in that, The concentration of the silane surface modifier in the ethanol solution of the silane surface modifier is 5-10 mg / mL, and the silane surface modifier is one of 3-aminopropyltriethoxysilane and 3-mercaptopropyltriethoxysilane or any combination thereof.

9. A superhydrophobic modified porous ceramic membrane, characterized in that, The superhydrophobic modified porous ceramic membrane is the superhydrophobic modified porous ceramic membrane prepared by any of the methods described in claims 1-8.

10. The application of superhydrophobic modified porous ceramic membrane materials in oil-water separation, characterized in that, The superhydrophobic modified porous ceramic membrane is the superhydrophobic modified porous ceramic membrane as described in claim 9.

Citation Information

Patent Citations

  • Method for modifying hydrophobicity of ceramic membrane, its application and its apparatus

    CN102423641B

  • A method for superhydrophobic modification of TiO2 based on ceramic membranes

    CN111635258B